Occupational stress amongmhealth professionals in Ahmadu Bello University Teaching Hospital (A.B.U.T.H.),Shika, Zaria, Nigeria - Ladan, Muhammad Awwal; Sani, Dalhat Khalid; Musa, Halima Abdul; Ogbeh, Mary; Muhammad, Fatima Ladan (West Africa College of Nursing, 2014)
This study was carried out to survey occupational stress among health professionals in Ahmadu Bello University Teaching Hospital (ABUTH),Shika, Zaria. The study was aimed at investigating the differences in perception of stress among different health professionals in ABUTH. The descriptive survey design method was used. Questionnaires were distributed based on availability to the different dusters o f health professionals in the study group. A sample size of 107 was used comprising 45 nurses, 48 doctors, 5 pharmacists, 3 physiotherapists and 6 medical lab scientists. The findings showed that most of the respondents (36.5%) were within the age range of 31-40 years and very few of them were aged 55 years and above. More than fifty six percent(56.7%) o f the total respondents were males. Seventy five percent (75%>) of the respondents stay long (7-1 0hours) at work which could be a contributing factor to the development of occupational stress in them. Most of the respondents (90.4%) were identified to be stressed due to work overload because the number of health professionals available to carry out a particular function is inadequate. Eighty percent (80%) of respondents exhibit anger and irritability while twenty seven percent (27%>) engaged in absenteeism when they are stressed up. A lot of respondents (78.8%) combat these signs and symptoms of stress by the use of physical exercise. The following measures were recommended to help prevent stress at work: respondents should ensure that the workload is in line with their capabilities and resources, jobs should be designed so that they provide meaning, there should be positive stimulation and opportunities for workers to use their skills, workers' roles and responsibilities should be clearly defined, communication within the work place should be dear and unambiguous, there should also be opportunities for career development and future employment prospects.